ANTIBACTERIAL ACTIVITY OF MARIGOLD FLOWER (TAGETES ERECTA L.) ETHANOL EXTRACT CREAM AGAINST STAPHYLOCOCCUS AUREUS - Cahyaningrum, Putu Lakustini; Widyantari, A.A A Sauca Sunia (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Acne is caused by inflammation and obstruction of the skin pores, which traps excess oil (acne vulgaris). The bacterium Staphylococcus aureus is the causative agent of acne. Treatment and prevention efforts can be made traditionally. Purpose: Testing the antibacterial efficacy of the marigold flower ethanol extract cream (Tagetes erecta L.) against Staphylococcus aureus. Method: This type of research is descriptive exploratory and experimental. Samples of ethanol extract from marigold flowers (Tagetes erecta L.) were formulated into three treatments, namely concentrations of 25%, 50%, and 100% with three replications. Antibacterial efficacy testing was carried out by the agar well diffusion method. Data analysis used One-way ANOVA and Tukey HSD tests. Result: The inhibition zones produced by the ethanolic extract of marigold flowers were 8.59 ± 0.047, 9.23 ± 0.026, and 10.23 ± 0.044 respectively. Thus, a higher concentration of the ethanolic extract of marigold flowers in the cream produced more significant inhibitory activity. Conclusion: The ethanol extract cream of marigold flower (Tagetes erecta L.) showed antibacterial activity against Staphylococcus aureus and is suitable to be applied as a cream for the traditional treatment of acne (acne vulgaris).